EKSTRAKSI PEKTIN DARI LABU SIAM - Dwi Daryono, Elvianto (Jurnal Teknik Kimia, 2012)
Squash have pectin content about 6,7%. The common usage of pectin is in food industry, farmation and cosmetics. This research aims of extracting pectin from squash with research variables: HCl concentrations (1, 1.5, 2, and 2.5 N) and extraction times (30, 60, 90 and 120 minutes). Conditions of operation: weight of squash is 0.25 kg, heated temperature of materials is 60 oC, heated time of materials is 6 hours, solvents temperature is 80 oC, solvent volume is 1 liters, ethanol concentration is 70% and speed turn is around 60 rpm. Research procedure is made of three steps: pretreatment of materials, extraction process, and result analysis. The best result:  extraction time at 2 hours with the concentration of HCl 2 N, where concentration of metoksil pectin highest is 6.57%. Key words: extraction, metoksil, pectin, squash